Review of the genus Aulidiotis Meyrick, 1925 (Lepidoptera: Gelechiidae) - Liu, Linjie; Li, Houhun (Zootaxa, 2016)
The genus Aulidiotis Meyrick, 1925 is reviewed. Aulidiotis trimaculata Li, sp. nov., A. recta Li, sp. nov. and A. biloba Li, sp. nov. are described as new. One possibly new species from Hainan is discussed but not formally named for lack of material. Aulidiotis bicolor Moriuti, 1977 is recorded for the first time in China, and A. phoxopterella (Snellen, 1903) is redescribed. Photographs of adults and genitalia are provided, along with a key to all the species of the genus and a map to exhibit the distribution of these species.